2020
DOI: 10.21014/acta_imeko.v9i3.766
|View full text |Cite
|
Sign up to set email alerts
|

A UME Kibble balance displacement measurement procedure

Abstract: <p>The redefinition of the kilogram in terms of Planck constant came into effect on 20 May 2019. The National Metrology Institute of Turkey (UME) realised the new definition by means of the oscillating magnet Kibble balance. The novel dynamical measurement procedure developed for Kibble balance in Turkey has the advantage of being less sensitive to environmental disturbances compared to the traditional Kibble balance experiments. Precise displacement measurements are performed either with Michelson or Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…As a result, an additional uncertainty may arise in the displacement measurements due to the temporal variations of the air refraction index. In [26] it has been shown that, these variations are negligibly small provided that the duration of the measurement is much larger than the fundamental period of the magnet assembly.…”
Section: Vertical Displacement Measurementsmentioning
confidence: 99%
“…As a result, an additional uncertainty may arise in the displacement measurements due to the temporal variations of the air refraction index. In [26] it has been shown that, these variations are negligibly small provided that the duration of the measurement is much larger than the fundamental period of the magnet assembly.…”
Section: Vertical Displacement Measurementsmentioning
confidence: 99%